Maternity Nurses' Perceptions of Implementation of the Ten Steps to Successful Breastfeeding. Issue 1 (January 2018) - Cunningham, Emilie M.; Doyle, Eva I.; Bowden, Rodney G.
Abstract: Objective: The purpose of this study was to determine maternity nurses' perceptions of implementing the Ten Steps to Successful Breastfeeding . Methods: An online survey and a focus group were used to evaluate perceptions of maternity nurses of implementing the Ten Steps to Successful Breastfeeding in an urban Texas hospital at the onset of the project initiation. Responses were transcribed and coded using Nvivo software. Thematic analysis was conducted and consensus was reached among the research team to validate themes. Results: Twenty-eight maternity nurses participated. Nurses perceived a number of barriers to implementing the Ten Steps to Successful Breastfeeding including nurse staffing shortages, variations in practice among nurses, different levels of nurse education and knowledge about breastfeeding, lack of parental awareness and knowledge about breastfeeding, culture, and postpartum issues such as maternal fatigue, visitors, and routine required procedures during recovery care that interfered with skin-to-skin positioning. Maternity nurses desired more education about breastfeeding; specifically, a hands-on approach, rather than formal classroom instruction, to be able to promote successful implementation of the Ten Steps. Conclusions: More education on breastfeeding for new mothers, their families, and healthcare providers was recommended. Nurse staffing should be adequate to support nurses in their efforts to promote breastfeeding. Skin-to-skin positioning should be integrated into the recovery period. Hospital leadership support for full implementation and policy adherence is essential. Challenges in implementing the Ten Steps were identified along with potential solutions. Abstract : Nurses are vital to successful implementation of the Ten Steps to Successful Breastfeeding. This study evaluated maternity nurses' perceptions of promoting the Ten Steps in the hospital setting and their suggestions for how to overcome barriers and challenges.